Synthesis of Tetrahydrocarbazole Derivatives of the Indol Alkaloids - Gocmenturk, Mustafa; Dimici, Neslihan; Akdag, Resmiye; Gundogdu, Cevher; Okay, Gurol; Ergun, Yavuz (Asian Journal of Chemistry, 2012)
The synthesis of the tetrahydrocarbazole derivatives 6 and 11 which can give rise to synthesize indole or carbazole alkaloids were described. Many new tetrahydrocarbazole derivatives have also been synthesized.